(untitled) (Herald of Journalism, 2022)
The article is devoted to the problems of clarifying the functional semantics of ironic manifestations in mass media. Throughout the whole history of its nature, irony has received a huge number of forms, that until now there has never been a classification that defines a clear line between irony and categories. The meaningful heterogeneity of the text with its ironic direction has the particularity that it is created by the journalist intentionally, with the aim of provoking a certain stylistic effect. The article is devoted to research functional semantics of ironic excerpts in mass media and their linguistic backgrounds, which they express. The opening of this concept of irony, describes by the identification of irony as a content conceptual cate- gory of text, allowing the journalist to come up with an emotionally-valued attitude to the displayed reality. Key words: Ironic pronouncements, media text, publicism